On the Question of Intergenerational Differences in the Social Well-Being of Adolescents: Life Position and Assessment of Threat Significance - Sobkin V.S; Kalashnikova E.A (Moscow State University of Psychology and Education, 2021)
The article examines the specifics of social well-being in teenagers based on the opinions of 4,837 middle and high school students obtained during an anonymous questionnaire survey in 2020. The questionnaire included closed questions about priorities in life values, emotional assessment of future prospects, plans for the future and assessment of the significance of threats from the social environment. When analyzing the empirical material, the influence of demographic and social stratification factors is considered. Special attention is paid to identifying the relationships between values, the clarity of plans, the assessment of life success and possible social threats, taking into account the influence of gender and age characteristics. Based on the data comparison of a monitoring questionnaire for students of grades 9 and 11 conducted in 2010 (993 respondents) and 2020 (1327 respondents), using mathematical procedures of factor analysis, the characteristic changes in the social well-being of adolescents were identified that have occurred over the past 10 years. Modern teenagers plan their future more carefully, and the complex of life values associated with self-realization in the educational, cultural and professional spheres is more significant to them. At the same time, the values associated with successful implementation in family life have become less significant; the possibilities to provide for oneself are assessed as real social risks, and the tendencies of infantilization are increasing. In general, the set of indicators of social well-being used in this work can be used in psychological and pedagogical programs to study the sociocultural features of socialization in students of adolescent and young age.